Education : Building on Indigenous Knowledge - Srikantaiah, Deepa (World Bank, Washington, DC, 2012)
Indigenous knowledge (IK) can act as a powerful tool in a learning environment to teach students. Conventional curricula, and achievement tests in many countries, however, do not support students' learning based on their IK. Learning environments need to be adapted to help students build on their indigenous communities' knowledge, and by recognizing students' culture and value systems. Educators can further this type of education by combining appropriate pedagogical techniques1. The note presents various strategies that can help educators recognize the IK that students bring with them to learning environments, and use this as a stepping-stone to help them succeed academically. In addition, three educational programs that have successfully integrated IK into their projects are highlighted.